Analysis and Design of a High-Risk Tiered Retaining Wall Using a Geosynthetic Reinforcement System - Kosalim, Valdy; Isparmo; Saptyanto, Krisandi; Rante Panganggi, Wira; Agrina, Dwi (Himpunan Ahli Teknik Tanah Indonesia, 2025)
Infrastructure development in Indonesia often faces rugged terrain and high seismicity, requiring advanced geotechnical solutions. One of the challenges lies in ensuring that an embankment can effectively withstand heavy loading conditions. Mechanically stabilized earth (MSE) walls provide a safe and efficient option to address these RSS with a total height of 26.95 meters based on a previous project. The structure is designed to withstand a large static surcharge load (up to 375 kPa) and a seismic load with a peak horizontal ground acceleration (kh) of 0.225g. The method employed is a limit equilibrium stability analysis using Janbu's simplified method of slices for non-circular failure surfaces, referring to the SNI 8460:2017 standard, and utilizing TensarSlope software. The selected system is the SierraScape System, which combines high-strength uniaxial geogrid primary reinforcement with a flexible welded wire for facing. The analysis results show that the retaining wall design meets the required factors of safety for both static (FS = 1.301 > 1.300) and seismic (FS = 1.163 > 1.100) conditions. In conclusion, this case study demonstrates that the application of modern geosynthetic reinforcement systems is a reliable and effective solution for addressing geotechnical challenges in high-risk projects in Indonesia, contributing a design reference for similar conditions.